2002
DOI: 10.1073/pnas.261705198
|View full text |Cite
|
Sign up to set email alerts
|

Order-sensitive plasticity in adult primary auditory cortex

Abstract: The neural response to a stimulus presented as part of a rapid sequence is often quite different from the response to the same stimulus presented in isolation. In primary auditory cortex (A1), although the most common effect of preceding stimuli is inhibitory, most neurons can also exhibit response facilitation if the appropriate spectral and temporal separation of sequence elements is presented. In this study, we investigated whether A1 neurons in adult animals can develop context-dependent facilitation to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 37 publications
5
68
0
Order By: Relevance
“…4B). The facilitation index is 100 times the logarithm base 2 of the ratio of number of responses to a CF tone under a two-stimulus paradigm and number of responses to a CF tone only (5). This method of analysis again confirmed that the average index of cortical sites with CFs centered at 7 kHz was positive and significantly larger than in control rats in the expected time of occurrence of the 7-kHz target stimulus if and only if it was preceded by the first target element (3 kHz) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4B). The facilitation index is 100 times the logarithm base 2 of the ratio of number of responses to a CF tone under a two-stimulus paradigm and number of responses to a CF tone only (5). This method of analysis again confirmed that the average index of cortical sites with CFs centered at 7 kHz was positive and significantly larger than in control rats in the expected time of occurrence of the 7-kHz target stimulus if and only if it was preceded by the first target element (3 kHz) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S uccessive-signal biasing ("prediction"), which is manifested in many behavioral studies in psychoacoustics and linguistics, very significantly contributes to the reception and production of rapidly successive inputs or actions (1)(2)(3)(4)(5). This study was designed to begin to reveal fundamental auditory system processes that could account for that biasing.…”
mentioning
confidence: 99%
“…The auditory response of AC neurons can be modulated by stimulus sequence (McKenna et al 1989;Brosch et al 1999;Brosch and Schreiner 2000), and some AC neurons respond selectively to a particular sequential combination of sounds (Suga et al 1978;Kilgard and Merzenich 2002;Nakahara et al 2004). These studies suggest that sound sequences can be coded by AC neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing either an FM sweep or a train of simple tones increased response strength and decreased the mean onset latency (Kilgard et al, 2001a;Mercado et al, 2001;Moucha et al, in press). Pairing complex stimuli, such as a spectral ripple or a tone-tone-noise sequence, decreased latency without affecting response strength (Kilgard and Merzenich, 2002;Kilgard et al, 2001b). No changes in response strength or latency were noted after two nearby tones were paired with NB stimulation.…”
Section: Changes In Cortical Excitability and Latencymentioning
confidence: 95%